Perinatal changes in estradiol and Ang II concentrations in pregnant women with pulmonary arterial hypertension and their correlation. (3rd July 2019) - Wang, Yanshuang; Che, Hao; Kang, Kai; Zhao, Guosheng; Li, Xiaoguang; Che, Xiangming; Xu, Mingjun; Zhao, Liyun
ABSTRACT: Objective : This study aimed to analyze the perinatal changes of plasma estradiol (E2 ) and angiotensin II (Ang II) in pregnant women with pulmonary arterial hypertension before and after cesarean section. Methods : Depending on pulmonary arterial pressure, the subjects were divided into two groups, moderate group, and severe group. Plasma concentrations of E2 and Ang II were determined at different time points using electrochemiluminescence immunoassay and ELISA, respectively. The correlation between E2 and Ang II concentrations was analyzed. Results : Intragroup comparison indicated that E2 levels at different time points after surgery decreased in the two groups than before, with a greater reduction in the severe group. Besides, both groups showed a reduction in Ang II concentrations after surgery. As indicated by intragroup comparison, there was a significant difference at each time point in the two groups. The reduction in Ang II concentrations was more conspicuous at 48 h and 72 h after surgery (cesarean section) than before for the two groups. Moreover, E2 concentrations were correlated positively with AngII concentrations. Conclusion : Plasma concentrations of E2 and Ang II decreased after delivery. The plasma concentrations of E2 and Ang II were correlated with each other.